2012
DOI: 10.5755/j01.ee.23.1.1228
|View full text |Cite
|
Sign up to set email alerts
|

Does Competence-Oriented Higher Education Lead to Students’ Competitiveness?

Abstract: According to the analysis of the stage of economic development of the countries reflected in “The Global Competitiveness Report 2010-2011” and conducted within the framework of the World Economic Forum, the EU countries have either innovation-driven economies or are in the transition stage from efficiency-driven to innovation-driven economies. Focusing on the educational aspects and human capital for further economic development of EU countries, quality higher education and training, business sophistication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…RMT's depiction of the assessment mode is consistent with the rational and analytical thinking foundation frequently linked to higher levels of education. Education is commonly associated with ‘skills’, particularly academic skills (Stasz, ), and indicates, to some degree, a person's cognitive base, knowledge, competence, and confidence (e.g., Oganisjana and Koke, ). More advanced levels of education have negative implications for individual action propensity because of the tendency of formal education to emphasize ‘left brain’ rational and analytical approaches over intuition, spontaneity, emotion, and flexibility in problem solving (Burke and Sadler‐Smith, ; Evans et al., ; Taggart and Robey, ).…”
Section: Hypothesesmentioning
confidence: 99%
“…RMT's depiction of the assessment mode is consistent with the rational and analytical thinking foundation frequently linked to higher levels of education. Education is commonly associated with ‘skills’, particularly academic skills (Stasz, ), and indicates, to some degree, a person's cognitive base, knowledge, competence, and confidence (e.g., Oganisjana and Koke, ). More advanced levels of education have negative implications for individual action propensity because of the tendency of formal education to emphasize ‘left brain’ rational and analytical approaches over intuition, spontaneity, emotion, and flexibility in problem solving (Burke and Sadler‐Smith, ; Evans et al., ; Taggart and Robey, ).…”
Section: Hypothesesmentioning
confidence: 99%
“…The research revealed that in both transition economies and industrial countries, scientists mostly analyse the impact of self-employment start-up factors, i.e. the factors that determine personal decision to act independently in the labour market (earle, Sakova 2000;andersson, Hammarstedt 2010;Blanchflower 2008;Leoni, Falk 2010;krasniqi 2009;Golpe, Stel 2007;Glocker, Steiner 2007;kim 2007;Oganisjana, koke 2012;Snieska, Venckuviene 2011;alvarez-Herranz et al 2011;Smaliukiene et al 2012;moreno et al 2010;Vázquez-Burgete et al 2012 and others), whereas the factors of self-employment duration as well as their impact on self-employment level are hardly covered in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of studies by Oganisjana and Koke (2012), the development of the competence of students (potential new employees) is closely related to the growth of their entrepreneurship. Based on that, according to the authors ( 2012), attention should be paid to the goal of contemporary higher education to develop students' entrepreneurship, which is understood as a dynamic system and is defined using not only such elements as knowledge, skills and attitudes, but also includes the individual's nature, features, experience, motivation and behaviour.…”
Section: Importance Of Employee Motivation and Work Pay In The Process Of Creation Of The Value Of A Business Companymentioning
confidence: 99%